Illegal Logging and Wood Consumption: Estimation and Projection of Illegal Wood Harvesting in Pakistan through System Dynamics - Naila Nazir (Corresponding author) (Pakistan Journal of Commerce and Social Sciences, 2017)
The scale and impacts of the illegal logging economy are an important and interesting area of research, which suffers from data deficiency that makes the analysis a challenging task, especially in developing countries. The present study is an attempt to estimate the illegal wood harvest from State forests in Pakistan, using a system dynamics model to simulate time series data from 1990-2010. Projections of illegal logging were made up to 2029-30. Depending on the global estimation criteria for illegal logging, the study incorporated legal harvest from the State forests in a system dynamics model with population growth as a driving force of wood consumption. The supply contribution of State forests to total wood consumption and wood actually harvested from State forests is set as a base to estimate the level of illegal wood harvest. The monetary value of illegally harvested wood is determined on the basis of forestry sector contribution to GDP. The results show that illegal wood harvest is 4 times more than the legal wood harvest, and after the harvesting ban this ratio has decreased over time with the increasing share of wood supply from farmlands.